An explorative study of the use of induction heating on the exhausting of canned ready-to-drink soybean (Glycine max) milk - De Leon, Juan Luis D.; Gonzales, Benjamin A. (Quezon City College of Home Economics, University of the Philippines Dilman, 2015)
ABSTRACT This study explored the use of direct induction heating (IH) as a viable substitute for the exhausting of canned soya bean (Glysine max) milk lieu of conventional exhausting methods involving steam or hot-water bath due to its higher energy efficiency and faster heating rate. Soya bean milk was prepared from raw materials and was subjected to exhausting using a modified household induction cooktop and other traditional methods for comparison. Exhausting processes were compared for cost and energy efficiency. The resulting products were also compared on the basis of physico-chemical and sensorial characteristics. One-way ANOVA at P=0.05 revealed that, generally, there were no detectable and measurable differences between the samples subjected to varying forms of exhausting in terms of physico-chemical and sensorial properties. In heating single cans, it was revealed that induction heating is 394% more cost effective than heating via LPG based on current Philippine rates for LPG and electricity. However, when factoring in the ability of LPG powered exhausting methods to process in bulk and the unavailability of technology to allow IH to process in bulk, it was revealed that when attempting to match equal output, LPG-powered methods outperformed IH by 200-600% in cost and consumption. It was concluded that at its current state and availability of technology, IH is not yet a viable substitute for the exhausting of canned goods. It is recommended that the study by continued and an induction heater capable of matching the output of traditional exhausting methods be developed and further explored.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Induction heating; Soymilk -- Preservation; Canning and preserving -- Philippines